2021
DOI: 10.1097/mlr.0000000000001603
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Unemployment and Health Insurance Coverage

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…[17][18][19] This study suggests that new Medicaid enrollment among newly unemployed workers was made more feasible with expanded Medicaid eligibility guidelines during the COVID-19 pandemic. In addition, the results support those of previous studies 5,20 describing the use of broader eligibility guidelines for Medicaid to facilitate unemployment-related Medicaid enrollment during economic downturns (eg, the Great Recession from 2007 to 2009) and the increased accessibility to Medicaid among those affected by local economic downturns after passage of the ACA. In combination with other recent studies, 6,21 we believe that this study's findings provide support for potentially stabilizing access to care through Medicaid expansion for households affected by job loss.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[17][18][19] This study suggests that new Medicaid enrollment among newly unemployed workers was made more feasible with expanded Medicaid eligibility guidelines during the COVID-19 pandemic. In addition, the results support those of previous studies 5,20 describing the use of broader eligibility guidelines for Medicaid to facilitate unemployment-related Medicaid enrollment during economic downturns (eg, the Great Recession from 2007 to 2009) and the increased accessibility to Medicaid among those affected by local economic downturns after passage of the ACA. In combination with other recent studies, 6,21 we believe that this study's findings provide support for potentially stabilizing access to care through Medicaid expansion for households affected by job loss.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the authors found that there was an increase in Medicaid enrollment associated with unemployment in expansion states compared with nonexpansion states. 20 In another study of COVID-19-related Medicaid enrollment in North Carolina, a nonexpansion state, Shafer et al 23 found unemployment-related enrollment to be more prevalent in communities with higher levels of prepandemic social vulnerability (eg, limited access to social services, lower levels of educational attainment, and housing insecurity). The risk of becoming uninsured after job loss was prevalent in both expansion and nonexpansion states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One found Medicaid expansions under the ACA led to increased Medicaid enrollment among the unemployed, and this increased coverage led to stark reductions in uninsurance among this group 26 . Another study found expanding Medicaid's eligibility guidelines increased the connectivity between declines in local economic conditions and Medicaid enrollment 27 . Another study using the HPS found declines in ESI were comparable in expansion and non‐expansion states over time, and non‐expansion states' overall decline in coverage was largely driven by reductions in ESI 28 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Another study found expanding Medicaid's eligibility guidelines increased the connectivity between declines in local economic conditions and Medicaid enrollment. 27 Another study using the HPS found declines in ESI were comparable in expansion and non‐expansion states over time, and non‐expansion states' overall decline in coverage was largely driven by reductions in ESI. 28 Focusing on trends in COVID‐linked racial disparities in Arkansas, Kentucky, Louisiana, and Texas (non‐expansion state), Figueroa and colleagues found the declines in coverage and access to care were smaller, though not statistically significant, in the three states with expanded Medicaid.…”
Section: Discussionmentioning
confidence: 99%